The economic and regulatory differences between professional football and ice hockey in Switzerland - Mustafi, Z.; Bayle, E.; Lang, M. (Sport in Society: Cultures, Commerce, Media, Politics, 2025)
Switzerland`s most prominent professional sports leagues are ice hockey`s Swiss National League and football`s Swiss Super League. Despite these leagues` importance within Swiss sport, their economic and regulatory landscapes have never been examined in detail. The present study addressed this research gap by comparing five key aspects of the two leagues: local potential, market environment, managerial expertise, marketing expertise, and regulatory oversight by governing bodies. Data analysis covering six seasons between 2014 and 2019 showed that the two leagues have adopted different regulatory paths within a form of passive competition in a relatively small country. The present study further contributes to the literature on these issues by proposing a general framework for comparing the regulation of professional sports in countries with two dominant professional team sports.